Galician Support for Miguel de Unamuno when He Was Banished to Fuerteventura - García Paz, Raimundo (Madrygal. Revista de Estudios Gallegos, 2020)
The spanish thinker Miguel de Unamuno “did not walk alone” when he was banished from Salamanca to Fuerteventura (Canary Islands) by the Dictatorship of Primo de Rivera in february 1924. Figures from Galicia together with characters associated with the massonery helped in his recepction in the island of the wind. The Bilbao-born philosopher turned to the surgeon José Goyanes Capdevila, native of Lugo, to connect with the powerful family Castañeyra, also from Lugo, who hosted him during his forced isolation. The present investigation reveals unknown data about his rugged journey to the archipelago and the four months of confinement he shared with Rodrigo Soriano, the radical federalist politician, equally from Basque country.
Keywords: Exile; Miguel de Unamuno; Castañeyra Family; Fuerteventura; Emilio G. López; José Goyanes Capdevila; Juan Madinaveitia; Ángel Ossorio y Gallardo; Rodrigo Soriano